The Effect of Fundamental Factors on The Stock Prices of Digital Banks in Indonesia - Ananta, Damar; Wulandari Pangestuty, Farah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The share price of Indonesia's digital banks declined and even stagnated in 2023 because their fundamentals were not as competitive as those of large banking companies. Investors eventually chose to sell these shares and prefer to invest in companies with more attractive fundamentals. The purpose of this research is to study how return on assets (ROA), return on equity (ROE), earning per share (EPS), price book value (PBV), and debt equity ratio (DER) impact the stock prices of several digital bank companies listed on the Indonesia Stock Exchange from 2021 to 2023. This study uses a quantitative approach and panel data regression analysis as the analysis method used in this study. The results of the analysis show that return on assets and debt equity ratio have no influence and are significant to the stock price of digital banks, while earning per share, and price book value have a positive and significant influence on the stock price of digital banks. In addition, the variable return on equity has no influence and is insignificant to the stock price of digital banks. All variables used in this study have a simultaneous influence on the share price of digital banks. Abstrak Harga saham bank digital Indonesia mengalami penurunan bahkan stagnan pada tahun 2023 karena fundamentalnya yang tidak kompetitif dibandingkan perusahaan perbankan besar. Investor akhirnya memilih menjual saham tersebut dan lebih memilih berinvestasi pada perusahaan yang fundamentalnya lebih menarik. Tujuan dari penelitian ini adalah untuk mempelajari bagaimana return on assets (ROA), return on equity (ROE), earnings per share (EPS), price book value (PBV), dan debt equity ratio (DER) berdampak terhadap harga saham beberapa perusahaan. perusahaan bank digital yang terdaftar di Bursa Efek Indonesia pada tahun 2021 hingga 2023. Penelitian ini menggunakan pendekatan kuantitatif dan analisis regresi data panel sebagai metode analisis yang digunakan dalam penelitian ini. Hasil analisis menunjukkan bahwa Return on Assets dan Debt Equity Ratio tidak mempunyai pengaruh dan signifikan terhadap harga saham bank digital, sedangkan Earning Per Share dan Price Book Value mempunyai pengaruh positif dan signifikan terhadap harga saham bank digital. Selain itu, variabel return on equity tidak mempunyai pengaruh dan tidak signifikan terhadap harga saham bank digital. Seluruh variabel yang digunakan dalam penelitian ini mempunyai pengaruh secara simultan terhadap harga saham bank digital.